Environmental Education Innovation: Transforming Household Waste for Sustainable Living - Raka Habib Sutanto; Yahya Rusmanat (Yayasan Sagita Akademia Maju, 2024)
This research explores how environmental education can be implemented using household waste, especially inorganic waste. Ecological education is an effort everyone makes to support environmental sustainability for sustainable survival. The increasing volume of waste demands serious attention to waste management. Waste management that is not environmentally friendly can hurt health and disrupt environmental functions such as settlements, forests, rice fields, rivers and oceans. Household waste, included in the inorganic waste category, is a source of pollution that is dangerous for the environment and human health because it consists of chemicals and cannot be renewed but is often ignored. Utilizing inorganic waste is one step all communities can take to preserve the environment. This research is descriptive and based on literature observations. Through sustainable environmental education, awareness of the importance of handling inorganic waste can increase in all levels of society.